2010
DOI: 10.1517/14728222.2010.525353
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β: friend or foe? The role of TGF-β/SMAD signaling in epigenetic silencing of ovarian cancer and its implication in epigenetic therapy

Abstract: Disruption of TGF-β/SMAD signaling leads to epigenetic silencing of its target genes transiently through histone modifications but permanently by promoter hypermethylation. Targeting the TGF-β signaling pathway may be a novel therapeutic strategy in ovarian cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 89 publications
1
40
0
Order By: Relevance
“…The so-far reported interactions between TGF-b and NF-kB in tumor cells provide a confusing view, with TGF-b playing the role of either an inhibitor or activator of NF-kB signaling in different cell types. Besides, although TGF-b acts as a potent tumor suppressor in normal ovarian surface epithelial cells, the loss of growth-inhibitory responses is an early event in ovarian cancer and yet TGF-b acts as a tumor-promoting agent in advanced ovarian cancer (37). On the basis of these data, it has been suggested that in the context of ovarian cancer, mutations and/or alterations of the key nodes along canonical TGF-b pathway shift TGF-b to noncanonical pathways such as activation of NF-kB which describes the pro-oncogenic role of TGF-b in advanced ovarian cancer (38,39).…”
Section: Discussionmentioning
confidence: 99%
“…The so-far reported interactions between TGF-b and NF-kB in tumor cells provide a confusing view, with TGF-b playing the role of either an inhibitor or activator of NF-kB signaling in different cell types. Besides, although TGF-b acts as a potent tumor suppressor in normal ovarian surface epithelial cells, the loss of growth-inhibitory responses is an early event in ovarian cancer and yet TGF-b acts as a tumor-promoting agent in advanced ovarian cancer (37). On the basis of these data, it has been suggested that in the context of ovarian cancer, mutations and/or alterations of the key nodes along canonical TGF-b pathway shift TGF-b to noncanonical pathways such as activation of NF-kB which describes the pro-oncogenic role of TGF-b in advanced ovarian cancer (38,39).…”
Section: Discussionmentioning
confidence: 99%
“…There are in essence three major groups of TGF signaling therapeutics: (1) ligand traps including monoclonal TGF neutralizing antibodies and soluble TGFRI/RII; (2) antisense molecule mediated silencing strategies for targeting TGF ligands; and (3) small molecule inhibitors targeting TGFRI/RII and downstream mediators (Chou et al, 2010;Iyer et al, 2005;Korpal & Kang, 2010;Nagaraj & Datta, 2010). Neutralizing antibodies are designed to disrupt the interactions between TGF ligands and their cell-surface receptors (Chou et al, 2010). Some of these include 2G7 and 1D11 monoclonal antibodies which hinder the activity of all three TGF ligands to reduce tumor growth and metastasis (Chou et al, 2010).…”
Section: Targeting the Tgfsignaling Pathway For Therapymentioning
confidence: 99%
“…Neutralizing antibodies are designed to disrupt the interactions between TGF ligands and their cell-surface receptors (Chou et al, 2010). Some of these include 2G7 and 1D11 monoclonal antibodies which hinder the activity of all three TGF ligands to reduce tumor growth and metastasis (Chou et al, 2010). GC1008 is yet another neutralizing antibody which entered a Phase I/II clinical trial for advanced malignant melanoma and renal cell carcinoma patients (Chou et al, 2010).…”
Section: Targeting the Tgfsignaling Pathway For Therapymentioning
confidence: 99%
See 2 more Smart Citations